Expanding the Horizons of Indonesian Literary Criticism: A Review of Ruang-Ruang Kemungkinan dalam Kritik Sastra Akademik by Saeful Anwar - Akmal, Ramayda (Humaniora, 2025)
This book serves as a significant contribution to the discourse on literary criticism in Indonesia by effectively addressing the gaps left by existing critical works. One of its strengths lies in its balanced analysis, which considers both structure and content while engaging in a thorough dialectical exploration of internal and external elements. Anwar’s writing style stands out for its flexibility, benefiting from his unique perspective as both an academic and a literary author. This dual identity allows him to maintain intellectual rigor without succumbing to the constraints of overly formal academic language.